Design creativity: refined method for novelty assessment. Issue 1 (3rd April 2019) - Jagtap, Santosh
Abstract: Novelty is an important characteristic of a creative idea, forming a core component of creativity. Measurement of novelty is therefore essential to assess creativity. We found deficiencies in a frequently cited method of novelty assessment found in the literature. We refine this method by proposing four modifications, supported by drawing on examples of products and ideas. The refined method and the original method are evaluated by benchmarking them against the collective, intuitive assessment of product novelty by experienced designers. The overall achievement of the refined method as presented in this paper is its contribution to a better assessment of product novelty.